Developing a Conceptual Framework for Student Learning during International Community Engagement - Pink, Matthew; Taouk, Youssef; Guinea, Stephen; Bunch, Katie; Flowers, Karen; Nightingale, Karen (Journal of University Teaching and Learning Practice, 2016)
University-community engagement often involves students engaging with people who experience multiple forms of disadvantage or marginalization. This is particularly true when universities work with communities in developing nations. Participation in these projects can be challenging for students. Assumptions about themselves, their professional practice, and broader society are tested while dealing with the challenges of life in a developing nation. In light of this, students’ learning and their personal well-being need to be supported before, during, and after participating in international community engagement . This paper reports on the development of a conceptual framework for the support and enhancement of student learning during international community engagement. The paper then reports on the development of a resource that aims to support student learning. Early pilot data suggested that the resource is effective in supporting student learning and well-being and that the resource shows potential for wider use in the higher education sector.